Pancasila Sebagai Solusi Terorisme - Izzati Khoirina Umami; Alia Nafisah Rahma; Moh. Faizin (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
This article focuses on an in-depth examination of the importance of Pancasila as a fundamental and long-term solution to the dangers of terrorism in Indonesia. Terrorism is a serious threat that endangers national unity and betrays universal human values, in addition to being a security issue that causes fear and confusion. In this work, we use a comprehensive literature review approach, examining various sources that discuss the close relationship between the noble values of Pancasila and planned efforts to combat the seeds of radicalism. The findings of this analysis clearly demonstrate the importance of Pancasila as the guardian of the nation's ideology. Its five principles, from belief in God to social justice, serve as an essential foundation for morality and ethics, shaping the character of the nation that upholds culture, justice, and tolerance. The nation's ideology will be more resilient against radical ideologies when these principles are internalized and applied systematically in daily life, the education system, and the formulation of public policy. To prevent, address, and eradicate the causes of terrorism in Indonesia, Pancasila not only serves as the foundation of the state but also as a guide for community life.